Effect of rice husk ash Si3N4 addition on the mechanical, wear, tensile fatigue and creep behaviour of a novel AA7475-TiB2 metal matrix composite - V. Pandiaraj; T. Ramesh; S. Muthukumaran (Discover Materials)
Abstract The growing demand for lightweight, high-strength materials in aerospace, automotive, and defense industries necessitates the development of advanced aluminum metal matrix composites (MMCs) with enhanced mechanical and tribological properties. This study presents the development of a novel AA7475 MMC using a combination of in situ and ex situ reinforcement methods. Agricultural biomass-derived ceramic filler (rice husk ash) was combined with in situ TiB2 and ex situ Si3N4 reinforcements to improve the composite’s performance. The in situ processing utilized K2TiF2 and KBF2 salts, while Si3N4 was externally introduced. The MMCs were fabricated via the stir casting method and characterized according to ASTM standards. Experimental results demonstrate that the composite with 3 vol.% Si3N4 and 5 vol.% TiB2 achieved the highest tensile strength of 486.56 MPa and peak hardness of 173.3 BHN. Additionally, the reinforced composite exhibited superior wear resistance, reduced coefficient of friction, and enhanced fatigue and creep performance. Microstructural analysis confirmed the uniform distribution of reinforcement particles, contributing to improved mechanical integrity. These findings highlight the potential of the developed AA7475-based MMCs for high-performance applications in automobile and aerospace applications.